STUDI TENTANG BUSANA PENGANTIN TRADISIONAL KURAI BUKITTINGGI - Yunus, Rona Rahayu; Efi, Agusti; Yuliarma, Yuliarma (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
This research is motivated by socio-cultural developments that occurred among the society and modernization in fashion design which includes models, materials, colors, and embellishments. These cause the changes intraditional fashion that should be conserved by the society who use it, one whichoccurred insociety at Kurai, Bukittinggi. The purpose of this research is to describe the design of traditional wedding dress of Kurai Bukittinggi in terms of models, materials, colors, embellishments and also describe the meaning of the philosophy contained in that traditional wedding dress of Kurai Bukittinggi. The method used in this research is descriptive qualitative method. This research was held in Kurai, Bukittinggi. Data which are collected in this research were taken from the observations, interviews, and documentations. This research also used the techniques of data analysis namely data reduction, data presentation and taking conclusion. To obtain valid data by doing an extension ofobservation, perseverance of observation, triangulation and auditing. The results of the research of traditional wedding dress in Kurai, Bukittinggi consists of the bridal clothes for the bride and bridegroom. The clothes of bridegroom consists of a suit, sarawa lambuak, sisampiang, cawek (waist belt), saluak, tie, karih (dagger), tungkek (stick), kampierokok, and tarompasapik (footwear). The clothes of the bride consists of a dress called bajukuruangbatabua, kodekbalapak, salendangbalapak, tokoksanggua, jewellery, tarompasaruang (footwear), and uncang (purse). The philosophy's meaning from traditional wedding dress generally contain the culture messages and the basic values of Islam teaching as stated in a proverb in Minangâ€œAdaik Basandi Syarak, Syarak Basandi Kitabullahâ€ and one of the wedding dress which is has a philosophy meaning is only the traditional wedding dress in Minang. Meanwhile the suit, shirt, and tie have no philosophy meaning because there is notÂ in Minang culture traditionally, however Western culture adopted into Minangkabau culture and used as a part of the wedding dress of Kurai, Bukittinggi. Â Kata Kunci: Busana pengantin tradisional, desain, makna filosofi, Kurai Bukittingi